Pemanfaatan Kembali Limbah Roti dalam Proses Produksi Makanan Reuse Of Bread Waste In Food Production Process - Nurtekto; Ni Komang Ayu Artiningsih (Universitas 17 Agustus 1945 Semarang, 2024)
The World Food and Agriculture Organization (FAO) said that one third of the food produced each year, amounting to 1.3 billion tonnes, is food waste. Food waste is food that is fit to be eaten before or after it has expired. Food waste is classified into two: food losse and food waste. food waste based on probability is probably avoidable waste, avoidable food waste, unavoidable food waste. Sampel for probably avoidable waste is breadcrump. But sampel for unavoidable food waste is solid tofu waste. The problem of food waste that has a negative impact on health and the environment can be reduced by utilizing it through the right processing process so that. Reusing food waste will also provide economic value. One of the wastes that can be consumed again but must use a different processing process is probably avoidable waste is the edge of bread that can be made into breadcrumbs, which is flour made from mashed dry bread and waste with the Unavoidable food waste category, for example, is tofu dregs that are reprocessed into tofu dregs flour.